Barreras y soluciones para la implementación de innovación en construcción de proyectos de energía y recursos naturales en Colombia (2020)
The innovative processes and systems in the energy and natural resources sector in Colombia bring relevant benefits to the projects where they are implemented, in terms of costs, efficiency in the use of resources, general quality and safety. However, it implies changes in mindset and in the way projects are carried out, accompanied by the need to have a consensus of wills with the actors involved, strong enough to achieve implementation and lead to success, which requires improvement. in technical, legal and economic standards issued by private (such as Hilti) and governmental actors, raising the general standard of the sector.